Impact of Cooking and Frying on Retention of Antioxidants in Sweet Potato (Ipomoea batatas) - Ogbonnaya Chukwu; Ndidiamaka G. Nwachukwu (Current Perspectives in Agriculture and Food Science Vol. 7, 2024)
Free radicals are chemicals that damage cells and cell membranes and are associated with the development of conditions like atherosclerosis, diabetic heart disease, and colon cancer. It is known that heat treatment can lead to physical and chemical changes that can decrease or alter the properties of food. This study determines the impact of cooking and frying on the antioxidants (vitamin A, vitamin C and vitamin E) present in sweet potato. The variety of sweet potato used is the orange type that was free from diseases and defects. Two of the commonest ways of processing sweet potatoes for consumption are cooking and frying. These methods of processing sweet potato for consumption make sweet potato palatable but they also have adverse impact on the proximate compositions of the sweet potato. Portions of prepared orange sweet potato samples were fried under a regulated temperature of 70oC for different time intervals of 10 minutes and 15 minutes while some other portions were cooked at 100oC for 10 minutes, 15 minutes and 20 minutes. Analysis of vitamin A, vitamin C and vitamin E contents was carried out on raw, fried and cooked sweet potato samples using the nutritional guidelines of Association of Official Analytical Chemists. Differences between the mean values of the treatments were determined by the least significant difference (LSD) test at 5% level of significance. There were significant differences in vitamin A, vitamin C and vitamin E contents of cooked and fried orange sweet potato. Both frying and boiling treatments resulted in a significant increase in vitamin A contents of orange sweet potato. In particular, the boiling process caused the higher reduction in the vitamin A contents of orange sweet potato. More of the nutritional contents, especially vitamins A and C were retained in cooked sweet potato than in fried one. Cooked sweet potato is recommended for the elderly and small children since it contains more vitamin A which enhances good eyesight. Consequently, boiling rather than frying may be recommended as a preferred processing option for orange sweet potato for human consumption.